DEVELOPMENT OF ARTICULATE STORYLINE-BASED INTERACTIVE MEDIA ON CONSTRUCTION DRAWINGS OF UTILITIES AND PLUMBING SYSTEMS - Mariza Nur Hazimah; Fadila Fitria Wulandari; M. Aris Ichwanto; Agil Fitri Handayani (LPPM Universitas Negeri Jakarta, 2025)
Vocational education seeks to prepare students with practical skills aligned with industry needs. One critical area is Building Modeling Design and Information (DPIB), which encompasses the development of digital learning media focused on construction utilities and plumbing systems. At SMK Negeri 11 Malang, student comprehension of this material has remained limited due to the lack of interactive media and restricted access to computing devices. This study aimed to design and implement a learning tool using Articulate Storyline software to improve students' understanding. Adopting a Research and Development (R&D) methodology, the study followed the ADDIE model for instructional design. Validation results indicated the media was highly feasible, with an average score above 80%. Effectiveness testing revealed a notable increase in student comprehension and learning motivation, with over 85% of participants responding positively. The media demonstrated strong potential to boost engagement and conceptual grasp. Future studies are encouraged to expand interactivity and incorporate game-based features to further enhance learning outcomes.